PENGARUH PRESENTASE KOMISARIS INDEPENDEN TERHADAP PERGANTIAN AUDITOR EKSTERNAL PERSPEKTIF FRAUD TRIANGLE THEORY - Ahmad Hijri Alfian; Achmad Zakki Baridwan (JURNAL STIE SEMARANG, 2020)
The purpose of this study is to examine the effect of the percentage of independent commissioners on the change of external auditors. Skousen (2009) study the percentage of independent commissioners is a proxy of Opportunity while the replacement of external auditors is a proxy of Rationalization. The Fraud triangle is the first theory discovered by Cressey (1953) who said that all cheating must be based on three things, namely pressure, opportunity and rationalization. The sample of this study was 42 companies that entered the LQ-45 registered in the Indonesian Stock Exchange in the period of 2017. The analytical method used to examine the effect of the percentage of independent commissioners on external auditor turnover was linear regression analysis. The results of this study indicate that the percentage of independent commissioners has a significant positive influence on the turnover of external auditors. In other words, the fewer the number of commissioners that are independent, the more likely the change in the external auditor before the normal time changes will be the more open the opportunity. Substitution of external auditors before 5 (five) years may be an initial indication of fraud at the company, because the steps to replace external auditors are very rare.